Meta-Learning: Learning to Learn in Machine Learning - Padmaja, T.V.S. (AG Volumes, 2024)
Within the deep learning domain, one of the most active study areas is meta-learning. There are several perspectives within the Artificial Intelligence (AI) community that support the hypothesis that meta-learning is a stepping stone towards the development of Artificial General Intelligence (AGI). Recent years have witnessed an increase in the creative development of meta-learning systems. The most recent research results are compiled in this book to provide readers a comprehensive grasp of meta-learning and how it could affect different machine learning applications. With the help of this technological description, meta-learning and its applicability to real-world problems are intended to progress.